Examination of Traditional Medicine and Herbal Pharmacology and the Implications for Teaching and Education: A Ghanaian Case Study - Asabere-Ameyaw, Akwasi; Sefa Dei, George J.; Raheem, Kolawole (Alberta Journal of Educational Research, 2010)
This article presents the preliminary findings of a pilot study of the practice, uses, and effectiveness of traditional medicine in Ghana. Based on in-depth interviews with local key practitioners and users of traditional medicine, the article points to some of the educational significance of local cultural knowledge on the environment and the relevance of such knowledge for science education in Ghana. In the discussion the authors briefly highlight general themes relating to local understandings of traditional medicine, the distinctions between traditional and plant medicine, contestations between traditional medicine and orthodox medicine, local conceptions of health and a healthy individual, the economics of health, and the lessons of science and public education. Although the findings of the study are preliminary, the article argues that much is to be gained for educational purposes through the critical study of traditional medicine, particularly in terms of the promotion of science and community education in Ghana.